The place of engraving in the creative work of graphic designer Mykola Stratilat - Petrushevska, Khrystyna; Stratilat, Mykola (Theory and practice of design, 2022)
The creative work of Professor Mykola Stratilat through the prism of ethnodesign worldview on the material of his album “Poetry in Images” is studied. Preliminary studies of the artist’s creative achievements are considered. Here are the main facts from the life of a graphic designer, which are directly related to his development as a holistic creative personality. The main motives in the work of the People’s Artist of Ukraine Mykola Stratilat are considered. A systematic analysis of the symbolic and figurative basis, artistic means and technological features, as well as individual works from the collection “Poetry in Images”. The life and philosophical position that became the driving force and make the works of Mykola Stratilat so original and unique are highlighted. The results of his creative achievements are summed up. The results of his creative achievements are summed up. The artist-designer has created more than 500 easel engravings, almost 200 bookplates, illustrated about 100 books, he is the author of watercolors, which have become iconic in the Ukrainian fine arts. In his work, Mykola Stratilat denies the sad reality not by outright protest, as the revolutionary sixties did, but by affirming everything positive, good and humane in the Ukrainian people. The artist is a real hero in the field of Ukrainian culture and art, because the beginning of his work dates back to the difficult times of Soviet totalitarianism, contempt for humanity, dignity and freedom. Mykola Stratilat’s work has been highly praised by art critics and scientists, such as Professors Dmytro Stepovyk, Yevhen Antonovych, Academician Mykola Zhulynsky, fellow artists Serhiy Yakutovych, Tetyana Golembievska, Valery Franchuk and others. Mykola Stratilat distinguished himself by creating reconstructions of architectural monuments of Ukraine, for which he received the honorary title of People’s Artist of Ukraine and was awarded the Order of St. Michael the Archangel of the Ukrainian Orthodox Church of the Kyiv Patriarchate. The purpose. To determine the place of creative contribution to the Ukrainian ethnodesign of the XXI century of the People’s Artist of Ukraine Mykola Stratilat and to conduct a systematic analysis of graphic and illustrative material in terms of book design on the example of his works from the album “Poetry in Images”. Methodology. The article uses traditional scientific methods of historical analysis, comparative analysis, the method of system-structural analysis. Results. The book illustration of Mykola Stratilat has been studied, the main features of his work have been singled out. Scientific novelty. For the first time, the creative work of Professor Mykola Stratilat is studied through the prism of ethnodesign worldview on the material of his album “Poetry in Images”. Practical significance. This material can be used in the cultural and educational process in the training of graphic designers.